2003
DOI: 10.1124/jpet.102.046219
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Selective Activation of μ-Opioid Receptor: Demonstrated with Deletion and Single Amino Acid Mutations of Third Intracellular Loop Domain

Abstract: The mechanism for the differential regulation of the -opioid receptor by agonists is investigated by identifying the receptor domains used to define the relative efficacies of three -opioid with Ala reduced the potency of DAMGO but not that of morphine PL017. Meanwhile, mutation of Thr 279 to Ala increased the potencies of morphine and PL017 but not that of DAMGO. The I278A mutation decreased the DAMGO coupling efficiency but increased the PL017 coupling efficiency. The R280A mutation resulted in the increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The deletion of the 276 RRITR 280 sequence from MOR (I35) resulted in decreased interaction with G␣ and the inability to mediate AC inhibition (28). The weaker interaction between I35 and G␣i2 was confirmed by the lesser amount of MOR or G␣i2 coimmunoprecipitated by each other (Fig.…”
Section: Mor Interaction With G␣i2 Determines the Location Of The Recmentioning
confidence: 79%
See 1 more Smart Citation
“…The deletion of the 276 RRITR 280 sequence from MOR (I35) resulted in decreased interaction with G␣ and the inability to mediate AC inhibition (28). The weaker interaction between I35 and G␣i2 was confirmed by the lesser amount of MOR or G␣i2 coimmunoprecipitated by each other (Fig.…”
Section: Mor Interaction With G␣i2 Determines the Location Of The Recmentioning
confidence: 79%
“…N2A cells with HA-MOR and MEF cells were cultured in DMEM with 10% FBS with or without 200 ng/ml G418. MOR mutants, with 276 RRITR 280 sequence in the third intracellular loop (I35) or the carboxyl tail sequence after Ser-363 deleted (363D), were generated, as described (28,30). Sense and antisense G␣i2 in pCDNA3 were transfected to HEK293 cells by using Effectene (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of the four to five amino acid clusters resulted in differential effects on the affinities of the agonists and antagonists and also on the potencies and coupling efficiencies of the three opioid agonists. Thus, these mutational studies suggested that the activation of -opioid receptor and interaction between the critical domains within the third intracellular loop and the G-proteins are agonist-selective (Chaipatikul et al, 2003). The study also suggested that differences in the agonist response were due to the relative spatial orientation of the amino acids within the intracellular domain after agonist binding in determining the efficiency of the receptor to activate the G-proteins.…”
Section: Transfected Systemsmentioning
confidence: 87%
“…Our attempts were specifically focused in the third loop of ␦-OR, because this region was implicated in direct G protein binding and activation (Chan et al, 1995;Georgoussi et al, 1997), arrestin binding (DeGraff et al, 2002), and ligand-selective activation (Chaipatikul et al, 2003). We found that cellular expression of a 23-amino acid polypeptide derived from the i3L of ␦-OR was able to target the opioid receptor as assessed by coprecipitation studies.…”
Section: Discussionmentioning
confidence: 99%
“…1A). The i3L domain has been shown to be critical for G protein coupling and activation (Merkouris et al, 1996; and to participate in receptor desensitization (Cen et al, 2001) and other aspects of signaling (Megaritis et al, 2000;Chaipatikul et al, 2003).…”
Section: Construction and Expression Of A Minigene Encoding The Thirdmentioning
confidence: 99%